Using mobile technology in teaching Grammar in Higher Education Institutions: The i-MoL Tool. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2013)
Today’s students are vastly different from the way they were a few decades ago. According to Eaton (2010), today’s students are tech-savvy. They can access a world of resources and information just at their finger tips. They are the creators, not simply consumers, of technology.